Innovación tecnológica en el ámbito electoral: el caso de la ONPE - Cucho, Mariano (2017)
This article reviews the most significant technological innovations developed by ONPE in recent years. These innovations were born based on the concepts of process management, results management, competencies management and the Malcolm Bridge performance excellence model implemented at the ONPE in 2014. The technological innovations developed in the institution on the basis of Information and Communication Technologies seek to improve services offered to citizens by following what the excellence in management model establishes. The article reflects that currently each of these technological innovations and their positive effects have yielded a high level of competitiveness in the organization, making it become an example of modernization for other public sector organizations in Perú.